2019
DOI: 10.1080/15384047.2019.1595279
|View full text |Cite
|
Sign up to set email alerts
|

Targeted blockade of HSP90 impairs DNA-damage response proteins and increases the sensitivity of ovarian carcinoma cells to PARP inhibition

Abstract: Pharmacological inhibition of PARP is a promising approach in treating high grade serous ovarian carcinoma (HGSOC). PARP inhibitors (PARPi) are most active in patients with defects in DNA damage repair (DDR) mechanisms, such as alterations in expression/function of DNA repair and homologous recombination (HR) genes/proteins, including BRCA1 and BRCA2. Benefit of PARPi could be extended towards HR-proficient patients by combining PARPi with agents that functionally abrogate HR. An attractive molecular target fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…Recent studies have revealed great potential of mTOR inhibitors in treating MCL (33)(34)(35). More importantly, recent studies have showed synergistic effects between mTOR inhibitors and CDK inhibitors in many cancers including MCL (36,37) (48). In addition, levels of p21, p27, CHK1, RAD51 and phosphorylated form of histone H2AX changed and activation of CHK2 was observed following ganetespib exposure in colorectal cancer (49).…”
Section: Pre-treatment Of Ganetespib Sensitize MCL Cells To Mtor Inhibitorsmentioning
confidence: 99%
“…Recent studies have revealed great potential of mTOR inhibitors in treating MCL (33)(34)(35). More importantly, recent studies have showed synergistic effects between mTOR inhibitors and CDK inhibitors in many cancers including MCL (36,37) (48). In addition, levels of p21, p27, CHK1, RAD51 and phosphorylated form of histone H2AX changed and activation of CHK2 was observed following ganetespib exposure in colorectal cancer (49).…”
Section: Pre-treatment Of Ganetespib Sensitize MCL Cells To Mtor Inhibitorsmentioning
confidence: 99%
“…Along with the improvements made in the knowledge of mechanisms underlying epigenetic regulation of gene expression, other molecular targets have been studied and exploited in order to turn HR-proficient HGSOCs into HR-deficient ones. Of note, attractive molecular targets are constituted by: the heat shock protein 90 (HSP90), which is an ATP-dependent molecular chaperone mediating the maturation, stability and activation of several hundreds of different proteins, including cell cycle regulators, such as CDK1, and key proteins essential for DNA repair, such as BRCA1, BRCA2, and RAD51 [76]; cyclin D1, a component of the cell cycle machinery which is involved in HR-mediated DNA repair and is overexpressed in 14-89% of ovarian cancer cases, resulting associated with a poorer prognosis [77]; vascular endothelial growth factor receptor 3 (VEGFR3), in which inhibition resulted in cell cycle arrest, decrease of both BRCA1 and BRCA2 expression, and significant increase of chemosensitivity in resistant ovarian cell lines in which a BRCA2 mutation had reverted to wild-type [78].…”
Section: Issues With the Management Of Hr Proficiency In Hgsocmentioning
confidence: 99%
“…37,38 As reported, STA-9090 inhibited cell growth by inducing cell cycle arrest in some cancers, including thyroid cancer, gastric cancer and ovarian cancer. [39][40][41] Here, we showed that STA-9090 strongly inhibited growth in MYC-overexpressed ESCC cells. However, STA-9090 did not benefit TE-1 cells with low MYC expression showing no cell-proliferation inhibition in vitro.…”
Section: Discussionmentioning
confidence: 70%